Exploring an Inquiry-based Approach to Enhance English Vocabulary Learning: Academy Students' Perspectives - Bahrain Kasuba; Anselmus Sudirman; Nanang Bagus Subekti (IJORER : International Journal of Recent Educational Research, 2023)
Objective: The objectives of this study are (1) to describe how the IBL approach can improve and motivate students to learn English vocabulary and (2) to explore how academy students believe the IBL approach has improved their English vocabulary. Method: This qualitative study investigates the application of the IBL approach and how students address its significance in learning activities at a Computer Science Academy in Ternate, North Maluku, Indonesia. This research sample randomly chose 15 academy students based on their IBL experience. Results: Using observation and interviews, the results show that students at the Computer Science Academy used the IBL approach toward learning English, vocabulary, planning activities, retrieving information, assignment processes, creativity skill development, and project sharing. Furthermore, students liked applying the IBL approach in the classroom, particularly in English lessons. The IBL approach also plays a crucial role in improving students' English vocabulary skills. Novelty: An essential aspect of using the IBL approach in vocabulary learning is something new that sheds light on the group collaboration process, creativity, and engagement.